Representación de grupos migrantes en los medios de comunicación impresos de Riobamba. Año 2021. - Orozco Allauca, Katherine Mishell (2023)
: In this investigation, a survey will be presented, about the representation of migrant groups in the printed media of Riobamba, during the year 2021, in the months of January, June and December that have been considered as references for analysis at three different moments of the period of study, in the newspapers Los Andes and La Prensa. The general objective was determined to study the representation of migrant groups in the print media of the city of Riobamba in the period 2021. The methodology used was qualitative; analytical and descriptive. The methods that were carried out were, the bibliographical verification, study of contents in which an analysis scheme was applied as a tool, for the study of journalistic genres, topics to be discussed and what is its purpose, while in the interviews , a semi-structured interview scheme was applied with the contribution of a general editor, a specialist in human mobility and a migrant, another instrument used was the representation scheme to determine the scope and origin of the migrant groups. In the results, it was determined that, there is a coverage of migrant groups in the print media, but its information is deficient, because it is no found a deeply analysis on the topics covered, by not having trained journalists for these areas and coverages, rather they make the guidelines and coverages based on what is happening on a day-to-day basis. Likewise, in the two newspapers it is observed that there is a reduction in publications since most of the news was about the vaccination against COVID -19.